Sistemas de alerta em um processo de enfermagem informatizado para Unidades de Terapia Intensiva - Barra, Daniela Couto Carvalho; Dal Sasso, Grace Teresinha Marcon; Baccin, Camila Rosália Antunes (Revista da Escola de Enfermagem da USP, 2014)
A hybrid study combining technological production and methodological research aiming to establish associations between the data and information that are part of a Computerized Nursing Process according to the ICNP® Version 1.0, indicators of patient safety and quality of care. Based on the guidelines of the Agency for Healthcare Research and Quality and the American Association of Critical Care Nurses for the expansion of warning systems, five warning systems were developed: potential for iatrogenic pneumothorax, potential for care-related infections, potential for suture dehiscence in patients after abdominal or pelvic surgery, potential for loss of vascular access, and potential for endotracheal extubation. The warning systems are a continuous computerized resource of essential situations that promote patient safety and enable the construction of a way to stimulate clinical reasoning and support clinical decision making of nurses in intensive care.